PENGARUH KOMUNIKASI DAN KOMPETENSI PEGAWAI TERHADAP KUALITAS PELAYANAN BPJS KETENAGAKERJAAN CABANG SEMARANG PEMUDA - Rizal Aditias; Hardi Warsono; Yuliana Kristanto (Journal of Public Policy and Management Review, 2021)
The purpose of this study was to determine: (1) results that cause the service quality of the BPJS Ketenagakerjaan subdivision Semarang Pemuda to be less than optimal; (2) what factors influence the less than optimal service quality of the BPJS Ketenagakerjaan subdivision Semarang Pemuda. This study uses a quantitative approach with an associative type of research. The population in this study were visitors to the BPJS Ketenagakerjaan subdivision Semarang Pemuda, with a total sample of 50 visitors. Data analysis techniques to determine respondents' perceptions of communication, competence, and service quality use frequency distribution tables, while to determine the magnitude of the influence of communication and competence on service quality using crosstab analysis, Kendall tau rank correlation coefficient, Kendall concordation coefficient, and determination coefficient with assistance SPSS IBM 25. The results of this study indicate the following: (1) there is a significant and positive relationship and influence between communication variables and service quality with a significance value of 0.000 (0.000 5.99). Communication and competence also have a positive influence on service quality by 0.720 or 72%.